Islamic Caring Behavior by Nurses on Patient Satisfaction: A Scoping Review - Noor, Farisha; Trisyani, Yanny; Mirwanti, Ristina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Caring behavior in nursing has an important role in improving patient satisfaction. Islamic caring behavior is not only limited to technical and professional aspects, but also includes spiritual and emotional dimensions in accordance with Islamic values. Purpose: The aim of this study is to explore how Islamic caring behavior is applied in nursing practice and its impact on patient satisfaction. Method: This study used a scoping review method by analyzing and synthesizing data from six relevant journal articles. The articles were selected based on specific inclusion criteria and analyzed to identify key themes related to Islamic caring behaviors in nursing. The databases used were PubMed, CINAHL, Scopus, and google scholar search engine. Results: The authors found 7 articles that discussed Islamic caring on patient satisfaction. Islamic caring behavior includes aspects of professionalism, empathy, patience, and spirituality. Factors that influence the implementation of Islamic caring behavior include nurse motivation, institutional support, and work environment. Specific activities such as prayer, recitation, and dhikr were also found to be integral to the practice of Islamic caring. In terms of impact, Islamic caring contributes to increased patient satisfaction through a more holistic approach to care. Conclusion: Integration of Islamic values in caring behavior can increase patient satisfaction in nursing services. The implication is that there needs to be greater recognition and support for the application of Islamic caring in nursing practice, both in terms of nurse education and health institutional policies.